Nineteenth-century communications
1 online resource
Keywords: This volume pays particular attention to Britain's embeddedness-and role in shaping-a rapidly expanding global communications network. In particular, it reflects the links between communications and Britain's imperial and colonial projects. It covers: The development of imperial communication routes and infrastructures as well as, in the late nineteenth-century, the introduction of imperial penny postage The ramifications of new technologies and media of communication for warfare and diplomacy between the end of the Napoleonic Wars and the beginning of the First World War Emigrants' correspondence The domestic significance of communication infrastructure in relation to British national identity The 1874 establishment of the Union Postale Universelle and related initiatives to globalise communications